Long-term effect of home-based pulmonary rehabilitation in severe asthma. (October 2019) - Grosbois, Jean-Marie; Coquart, Jeremy; Fry, Stephanie; Le Rouzic, Olivier; Grosbois, Thomas; Wallaert, Benoit; Chenivesse, Cecile
Abstract: Introduction: Home-based pulmonary rehabilitation (PR) has demonstrated its effectiveness amongst patients with chronic obstructive pulmonary disease (COPD) but has never been investigated in severe asthma. Methods: In a retrospective study, we included 28 patients with severe asthma (61.5 ± 16.2 years, FEV1: 51.4 ± 17.3%) and 164 matched COPD patients (64.3 ± 11.6 years, FEV1: 47.7 ± 15.5%) who had completed a home-based PR program and pursued at least 12 months of follow-up. The number of steps performed during a 6-min stepper test (6MST), the Hospital Anxiety and Depression (HAD) scores, and the Visual Simplified Respiratory Questionnaire score (VSRQ) were compared between baseline, the post-PR period (post-PR) and after 12 months of follow-up (M12) within each group. The evolution of the 6MST, HAD and VSRQ values between baseline, post-PR and M12 was compared between severe asthma and COPD patients. Results: In the severe asthma group, the 6MST was higher post-PR (504 ± 150, p = 0.043) and at M12 (538 ± 163, p = 0.016) compared with baseline (450 ± 148). The VSRQ score was higher at M12 (39.0 ± 18.6, p = 0.049) but not post-PR (38.7 ± 15.8, p = 0.119) in comparison with baseline (32.2 ± 12.4). There was no difference in the HAD scores between baseline, post-PR and M12. PR outcome was not significantly different between severe asthma and COPD patients at short and long term (p > 0.05). Conclusion: In severe asthma, home-based PR is associated with improved exercise tolerance and quality of life on a long-term basis but does not modify anxiety and depression. Highlights: Home-based PR improves exercise tolerance and quality of life in severe asthma. The effect of home-based PR in severe asthma and matched COPD patients is similar. The effect of PR is maintained up to 12 months after the PR program. Home-based PR does not modify anxiety and depression in severe asthma.